Molecular modelling and bonding - Moore, Elaine (Elaine A.) (Molecular world., 2002)
Why do molecules adopt particular shapes? What determines the physical and chemical properties of a material? Molecular Modelling and Bonding answers these questions by introducing the ideas behind molecular and quantum mechanics, using a largely non-mathematical approach. Atomic and molecular orbitals, computational chemistry and bonding in solids are also discussed. A Case Study, Molecular Modelling in Drug Design, explores ways in which computer modelling, in conjunction with experimental techniques, is used to design new drugs. The accompanying CD-ROM illustrates applications of molecular and quantum mechanics, and includes many of the structures and orbitals illustrated in the text. It provides the programs necessary to view orbitals and 3D structures. The Molecular World series provides an integrated introduction to all branches of chemistry for both students wishing to specialise and those wishing to gain a broad understanding of chemistry and its relevance to the everyday world and to other areas of science.